حماية الموارد المائية في ضوء القواعد الفقهية والأصولية - مجيدي, العربي; مجيدي, المانع; طويطي عبد القادر, عبد القادر (جامعة الوادي - University of Eloued, 2021)
يعدّ هذا البحث من البحوث التي تسلّط الضوء على قضية الموارد المائية؛ التي تُعتبر أساس كلّ حيٍّ في هذا الكون الفسيح، وكيفية حمايتها من خلال ربطها بالشريعة الإسلامية ممثّلةً في القواعد الفقهية والأصولية، والهدف منه التأكيد على أنّ الشريعة الإسلامية صالحة لكلّ زمان ومكان، والردّ على من يتّهمها بالقصور، والعناية بالقواعد الفقهية والأصولية ومعرفتهما؛ لما لهما من تأثير كبير في تيسير التعامل مع المستجدّات الحاصلة في حياة النّاس. ومن أهمّ النتائج المُتَوصّل إليها بيان أهميّة الموارد المائية في الشريعة الإسلامية، وعِظَم مكانتها، والتأكيد على أنّ الإسلام عُني بالحفاظ على الموارد المائية وحمايتها، ويُوصَى بعدم تلويثها؛ لأنّ في تلويثها إهلاك للكائنات الحية، وضرورة تخصيص ندوات وملتقيات تُوضّح خطورة فقدان هذا المورد الهام This research sheds light on the issue of water resources; which is the basis of every living thing in this vast universe. It tends to protect it by linking it to Islamic law, represented in the rules of jurisprudence and fundamentalism. The aim is to confirm that Islamic law is valid for every time and place, and to respond to those who accuse it of shortcomings. It also pays attention to know jurisprudential and fundamental rules because of their great impact in facilitating the handling of new developments in people's lives. One of the most important findings is to demonstrate the importance of water resources in Islamic law and their great standing, and to emphasize that Islam is concerned with the conservation and protection of water resources, and it is recommended that they not be polluted them, because they pollute the destruction of living beings and the need for seminars and meetings that illustrate the risk of losing this important resource
Protection of Water Resources in the light of Jurisprudence and Fundamental Principles
مقال
Keywords: حماية؛ الموارد المائية؛ القواعد؛ الفقهية؛ الأصولية: protection; Water Resources; the rules; jurisprudence; fundamentalism